Highly efficient transduction of human plasmacytoid dendritic cells without phenotypic and functional maturation - Veron, Philippe (BioMed Central, 2009)
BACKGROUND: Gene modified dendritic cells (DC) are able to modulate DC functions and induce therapeutic immunity or tolerance in an antigen-specific manner. Among the different DC subsets, plasmacytoid DC (pDC) are well known for their ability to recognize and respond to a variety of viruses by secreting high levels of type I interferon. METHODS: We analyzed here, the transduction efficiency of a pDC cell line, GEN2.2, and of pDC derived from CD34+ progenitors, using lentiviral vectors (LV) pseudotyped with different envelope glycoproteins such as the vesicular stomatitis virus envelope (VSVG), the gibbon ape leukaemia virus envelope (GaLV) or the feline endogenous virus envelope (RD114). At the same time, we evaluated transgene expression (E-GFP reporter gene) under the control of different promoters. RESULTS: We found that efficient gene transfer into pDC can be achieved with VSVG-pseudotyped lentiviral vectors (LV) under the control of phoshoglycerate kinase (PGK) and elongation factor-1 (EF1α) promoters (28% to 90% of E-GFP(+ )cells, respectively) in the absence of phenotypic and functional maturation. Surprisingly, promoters (desmin or synthetic C5–12) described as muscle-specific and which drive gene expression in single strand AAV vectors in gene therapy protocols were very highly active in pDC using VSVG-LV. CONCLUSION: Taken together, our results indicate that LV vectors can serve to design pDC-based vaccines in humans, and they are also useful in vitro to evaluate the immunogenicity of the vector preparations, and the specificity and safety of given promoters used in gene therapy protocols.